High Order Thinking Skill and Literacy Base Technological Pedagogical Content Knowledge (TPACK) in Order to Improve Students Learning Quality of in Job Primary School Teacher’s Proffesional Educational Program - Tatat Hartati; Dwi Heryanto; Nuri Annisa; Risma Nuriyanti; Alpin Herman Saputra; Rahmat Sutedi (International Journal of Science and Applied Science: Conference Series, 2019)
Quality of learning by teachers nowadays, have not became a serious focus of interest. As the result, the quality of the graduate student is at low rate. The purpose of this research is to develop and apply Technology Pedagogical Content Knowledge (TPACK) for the Injob Primary School Professional Educational Teacher Program (PPG dalam jabatan). The methods applied on the study were combination of qualitative and quantitative and R&D by 4D outline modification, they are; define, design, develop, and disseminate. The subjects of the study are 42 students of The Student of the Injob Teacher of Professional Educational Program which divided into two class of control and experiments each within 21 students. The result of the study is a TPACK model base on literacy and high order thinking skill with significance of the pretest and  posttest achievement at 0.001, which indicates that literacy base TPACK  model and  high order thinking skill effects to the quality of the Injob Teacher Professional Educational Program learning as the student experience Literacy base TPACK  model and high order thinking skill learning.